Sistem Informasi penjualan Kerajinan Tangan Restu Ibu Desa Bandar Tinggi Berbasis Web - Indriani, Siti Faujiah (Journal of Computer Science and Information System(JCoInS), 2021)
Internet media is currently used as a marketing medium in selling products such as social media and websites. The problems experienced by the Restu Ibu business currently underway are the process of marketing and promoting handicraft products which have been carried out by word of mouth and door to door, so that handicraft products are only marketed in Bandar Tinggi Village and surrounding areas. By using internet technology, the sales transaction process can be carried out without having to meet directly or find a place of sale directly. With the support of existing information technology, data processing currently carried out can be replaced with a web-based system. Data collection methods used are observation, interview (interview), and literature study. The programming used is website programming using MySQL and PHP databases. This research resulted in a Web-based Restu Handicraft Sales Information System at Desa Bandar Tinggi.